2002
DOI: 10.1021/ic0108484
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Optical Spectroscopy of Na3[Ln(dpa)3]·13H2O with Ln = Er3+, Tm3+, Yb3+

Abstract: The title compounds were synthesized and studied by solution and single-crystal absorption, luminescence, and excitation spectroscopy. The f-f luminescence is induced in the Tm(3+) and Yb(3+) complexes in solution by exciting into the (1)Pi-(1)Pi absorptions of the ligand in the UV. A single-configurational coordinate model is proposed to rationalize the nonradiative relaxation step from ligand-centered to metal-centered excited states in [Yb(dpa)(3)](3-) (dpa = 2,6-pyridinedicarboxylate). Direct f-f excitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
162
1
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(178 citation statements)
references
References 28 publications
11
162
1
4
Order By: Relevance
“…[17] Firstly, we recorded the ESI mass spectrum of [CrErCr(L1) 3 ](CF 3 SO 3 ) 9 in acetonitrile, and unambiguously confirmed that the kinetically inert ions [CrErCr(L1) 3 ] 9+ remain intact in solution for concentrations larger than 10 À4 m ( Figure S9). [12] provides similar upconversion luminescence, also with an exact quadratic dependence (I / P 1.98 (2) , Figure S10).…”
Section: +mentioning
confidence: 76%
“…[17] Firstly, we recorded the ESI mass spectrum of [CrErCr(L1) 3 ](CF 3 SO 3 ) 9 in acetonitrile, and unambiguously confirmed that the kinetically inert ions [CrErCr(L1) 3 ] 9+ remain intact in solution for concentrations larger than 10 À4 m ( Figure S9). [12] provides similar upconversion luminescence, also with an exact quadratic dependence (I / P 1.98 (2) , Figure S10).…”
Section: +mentioning
confidence: 76%
“…61 The total splitting value (Δ = 880 cm -1 for Yb(OSi(OtBu) Figure S32). [59][60][61][62][63] Finally the lifetime of the Yb(III) excited state was determined for all molecular complexes in solution and in the solid state (Table 5). In each case a perfect mono-exponential decay (eq 8) is observed with a lifetime between 5 and 5.8 µs (Figures S33 and S34).…”
Section: Molecular and Computational Modelsmentioning
confidence: 99%
“…Esse processo de conversão de luz, chamado de efeito antena, envolve a absorção de radiação ultravioleta através dos ligantes, que atuam como "antenas", a transferência de energia do estado excitado do ligante para os níveis 4f do íon metálico e a emissão de radiação no visí-vel, característica do íon metálico 9 . Dentre os diversos ligantes orgânicos que são usados na sínte-se de compostos de coordenação de íons lantanídeos, diversos trabalhos têm sido desenvolvidos com ligantes tridentados derivados de ácidos dicarboxílicos [10][11][12][13][14][15] ; n=6-15 moléculas de água) foram preparados segundo procedimentos descritos na literatura 18,19 .…”
Section: Introductionunclassified